Aristóteles y las series causales infinitas en Física VII y VIII - Alberto Ross (Tópicos, 2013)
The aim of this paper is to show that we have at least two different arguments that prove the First Motor's existence. Even though there are coincidences between Physics VII 1 and VIII 5, their arguments are not identical. Physics VII argue the impossibility of an infinite movement in a finite time and VIII 5 the necessity of a "principal" cause.